Comparison of Serum Cholinesterase and Plasma Cholinesterase Levels in Oil Palm Farmers Using Pesticides - Hartini H; Adillah Kurnia Hasanah (Riviera Publishing, 2025)
Pesticide exposure is a significant health concern for oil palm farmers, potentially leading to cholinesterase enzyme inhibition, which can serve as a biomarker for pesticide poisoning. However, the differences in cholinesterase levels between serum and plasma specimens in exposed farmers remain underexplored. This study aims to compare cholinesterase levels in serum and plasma samples from 15 oil palm farmers with at least five years of pesticide exposure. A cross-sectional research design was used, with blood samples collected from the farmers and analyzed for cholinesterase activity using photometric methods. The results showed no statistically significant difference between serum and plasma cholinesterase levels (p>0.05), indicating that both specimens are equally valid for monitoring pesticide-induced toxicity. Factors such as incomplete use of personal protective equipment (PPE) contributed to decreased cholinesterase levels, with the majority of farmers not utilizing full PPE during pesticide application. These findings suggest the importance of improving safety protocols, including proper PPE use and training, to protect farmers from the harmful effects of pesticides. Future research should explore the long-term health impacts of chronic pesticide exposure and assess the effectiveness of educational programs on PPE compliance to reduce pesticide-related health risks.